(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: Proliferative diabetic retinopathy (PDR) can cause a loss of vision due to complications like vitreous hemorrhage and tractional retinal detachment, which require vitrectomy. The source of bleeding is usually in pathologic new blood vessels in the fibrovascular epiretinal membrane (ERM). Anti-vascular endothelial growth factor agents are widely used for prevention of intraoperative and postoperative hemorrhagic complications in vitrectomy for PDR. Purpose: To examine ultrastructural features of ERM after intravitreal injection of various doses of aflibercept in patients with PDR. Material and Methods: Five patients (5 eyes) were included in the study. ERM specimens with neovascular vessels were taken intraoperatively from the five patients for histological microscopy studies. Specimen No. 1 was taken from the ERM (control ERM) of the patient who did not receive preoperative injection of aflibercept. In addition, specimen No. 2 was taken on day 3 after intravitreal injection of 1.0 mg aflibercept; specimen No. 3, on day 5 after intravitreal injection of 1.0 mg aflibercept; specimen No. 4, on day 3 after intravitreal injection of 2.0 mg aflibercept; and specimen No. 5, on day 5 after intravitreal injection of 2.0 mg aflibercept. Results: We found that aflibercept had a positive effect on obliteration of newly formed vessels and capillaries. There was a decrease in the size of the lumen of ERM microvessels with an increase in the injected dose and time after injection. In addition, endothelial cells in the newly formed vessels and fibroblasts exhibited active protein synthesis metabolism on day 3 after intravitreal injection of 1.0 mg aflibercept or 2.0 mg aflibercept.